Virtual oscillator with delayed feedback for transient mitigation in inverter-based islanded microgrids - Salim, Sanjna; Babu, Chembathu Ayyappan; Krishna, Bindu Murali (International Journal of Renewable Energy Development, 2024)
In recent years, the conventional control schemes for renewable energy-based inverter-dominated microgrids have been expeditiously replaced by Virtual Oscillator-based Control (VOC). The method of VOC ensures fast synchronisation and efficient load-sharing capabilities in inverter-based renewable energy systems. This work evaluates the effectiveness of VOC-based inverters in mitigating the transient dynamics of power system parameters like voltage, frequency and current under different types of switching events involving active and reactive load combinations. Further, to enhance the control efficiency of VOC under such load-switching scenarios a modified form of VOC is proposed utilizing the ability of the feedback mechanism to strengthen the state space trajectory of dynamical systems. In the proposed method, the control oscillator of conventional VOC driven by the inverter current is modified by providing a feedback signal in the form of an integral function of the error between the drive oscillator and the trajectory of the inverter output. The efficiencies of different forms of feedback are quantified in terms of percentage deviation in power system parameters as well as THD. The proposed feedback strategy can improve the control performance by bringing down the voltage deviation from 57 % in conventional VOC to around 4%. Likewise, the frequency deviation is brought down to 0.14% from 19.26 %. These advantages are achieved without any significant adverse impact on the THD. The proposed approach can be utilized in multi-inverter-based systems serving sensitive loads in microgrids.